Effect of land-use on the earthworm assemblages in semi-deciduous forests of Central-West Ivory Coast - Tondoh, Jérôme E.; Guei, AM; Csyzdum, C; Okoth, Peter F. (Springer, 2011)
In this study, the impact of forest disturbance on earthworm assemblages was assessed using monoliths dug out at 5 m intervals along a gradient of land-use intensification. The land-use types comprised primary forest (as a baseline), secondary forest, tree plantation, fallow, perennial and annual crop. Forest disturbance resulted in a significant decrease in soil organic carbon and pH, while earthworm abundance and biomass increased along the gradient of disturbance. Surprisingly, anthropogenic disturbances in semi-deciduous forest areas have not led to the disappearance of native species to the benefit of exotic species as revealed in former studies. As a result, in this study land-use change had no impact on species richness at the landscape level, even if at local scales, recurrent Chromolaena odorata fallows, multispecies tree plantations and 4 year-old teak plantations hosted the highest average species richness. Multiple regression analyses performed between earthworm communities and environmental variables showed that soil organic carbon and pH are potential indicators of earthworm abundance change.